Stress fractures - Migliorini, S.; Merlo, M. (Triathlon Medicine, 2019)
Stress fractures are a common cause of injury in triathletes. There is a spectrum of bone response to repetitive stress: normal response, stress reaction, and stress fracture. Physicians should maintain a high index of suspicion for stress fracture in triathletes presenting with insidious onset of focal bone tenderness associated with recent changes in training volume or intensity. Accurate and timely diagnosis and treatment are essential in the care of the athlete with stress fracture. Imaging, particularly MRI (magnetic resonance imaging), is often utilized to supplement the history and the physical examination. Poor training technique and a variety of extrinsic and intrinsic risk factors, including RED-S (relative energy deficiency in sports), may predispose triathletes to stress fractures. To provide treatment and prognostic parameters, it is important to classify stress fractures as high risk versus low risk, based on the anatomic location of the fracture and the natural history of fractures occurring at this anatomic site. It is particularly important to recognize "high-risk" fractures, as these are associated with an increased risk of complications. The best form of treatment for stress fracture is prevention. Any contributing factors, such as biomechanical abnormalities, anatomy, gender, nutrition, equipment, and running terrain, should be addressed.